Horrible Harry and the ant invasion - Kline, Suzy.; Remkiewicz, Frank (New York, N.Y., U.S.A. : Viking Penguin/Puffin, 1989)
Horrible Harry of classroom 2B cuts back on his mischievous pranks after falling for Song Lee.
"Ages 7-10"--P. [4] of cover.
School Library Journal
Booklist
2.5 - 4.2
3-6
Keywords: Schools -- Fiction; School stories